Interrater reliability of the Fugl-Meyer Motor assessment in stroke patients: a quality management project within the ESTREL study - Wiesner, Karin; Schwarz, Anne; Meya, Louisa; Kaufmann, Josefin Emelie; Traenka, Christopher; Luft, Andreas Rüdiger; Held, Jeremia Philipp Oskar; Engelter, Stefan (Frontiers in Neurology, 2024)
Introduction: The Fugl-Meyer Motor Assessment (FMMA) is recommended for evaluating stroke motor recovery in clinical practice and research. However, its widespread use requires refined reliability data, particularly across different health professions. We therefore investigated the interrater reliability of the FMMA scored by a physical therapist and a physician using video recordings of stroke patients. Methods: The FMMA videos of 50 individuals three months post stroke (28 females, mean age 71.64 years, median National Institutes of Health Stroke Scale score 3.00) participating in the ESTREL trial (Enhancement of Stroke Rehabilitation with Levodopa: a randomised placebo-controlled trial) were independently scored by two experienced assessors (i.e., a physical therapist and a physician) with specific training to ensure consistency. As primary endpoint, the interrater reliability was calculated for the total scores of the entire FMMA and the total scores of the FMMA for the upper and lower extremities using intraclass correlation coefficients (ICC). In addition, Spearman`s rank order correlation coefficients (Spearman`s rho) were calculated for the total score and subscale levels. Secondary endpoints included the FMMA item scores using percentage agreement, weighted Cohen`s kappa coefficients, and Gwet`s AC1/AC2 coefficients. Results: ICCs were 0.98 (95% confidence intervals (CI) 0.96-0.99) for the total scores of the entire FMMA, 0.98 (95% CI 0.96-0.99) for the total scores of the FMMA for the upper extremity, and 0.85 (95% CI 0.70-0.92) for the total scores of the FMMA for the lower extremity. Spearman`s rho ranged from 0.61 to 0.94 for total and subscale scores. The interrater reliability at the item level of the FMMA showed (i) percentage agreement values with a median of 77% (range 44-100%), (ii) weighted Cohen`s kappa coefficients with a median of 0.69 (range 0.00-0.98) and (iii) Gwet`s AC1/AC2 coefficients with a median of 0.84 (range 0.42-0.98). Discussion and Conclusion: The FMMA appears to be a highly reliable measuring instrument at the overall score level for assessors from different health professions. The FMMA total scores seem to be suitable for the quantitative measurement of stroke recovery in both clinical practice and research, although there is potential for improvement at the item level.